New Genes Born-In or Invading Vertebrate Genomes - Herrera-Úbeda, Carlos; Garcia-Fernàndez, Jordi (Frontiers in Cell and Developmental Biology, 2021)
Which is the origin of genes is a fundamental question in Biology, indeed a question older than the discovery of genes itself. For more than a century, it was uneven to think in origins other than duplication and divergence from a previous gene. In recent years, however, the intersection of genetics, embryonic development, and bioinformatics, has brought to light that de novo generation from non-genic DNA, horizontal gene transfer and, noticeably, virus and transposon invasions, have shaped current genomes, by integrating those newcomers into old gene networks, helping to shape morphological and physiological innovations. We here summarised some of the recent research in the field, mostly in the vertebrate lineage, showing that the placenta, the adaptative immune system, or the highly developed neocortex, among other innovations, originated after de novo gene creation or domestication of virus and transposons. We provocatively suggest that the high tolerance to virus infections by bats may also be related to previous virus and transposon invasions in the bat lineage.